Erfunden / Gefunden Potsdamer Vorlesungen zur Entstehung der Amerikas - Ette, Ottmar (AULA, 2022)
During the genesis of the Americas, "invention" was not the same thing as "discovery": what was invented preceded what was found and changed that discovery to the extent that both mutually permeated each other. This formed the foundation for both the indigenous population and their "discoverers," for deported slaves and for procured coolies. This lecture volume traces this process in detail, which still continues to this day.